(3GdcaGAI GdGfJGLjI ddefTBJ GdUfGYjI(B((3GdJcdaI(B-(3GdhbJ(B-(3GdCOGA(B) /s - (3GdeUQj, CMeO eMeOs ((3GdGScfOQjI(B: s (3eDSSI THGH GdLGeYI(B, s, 2004)
(3eaghe GdcaGjI GdEfJGLjI,GdJYQja HhSGFd bjGS GdcaGjI GdEfJGLjI,GdhSGFd GdeHGTQI dbjGS GdcaGjI GdGfJGLjI,GdhSGFd GdeHGTQI dbjGS GdcaGjI GdEfJGLjI ddBdGJ hGdJLgjRGJ GdBdjI,GdhSGFd GdeHGTQI dbjGS GdcaGAI GdEfJGLjI ddYed,GdhSGFd ZjQ GdeHGTQI dbjGS GdcaGjI GdEfJGLjI,JWHjbGJ YedjI aj GdUfGYGJ GdZPGFjI GdeUQjIs
(3HHdhZQGajG(B: (3U(B.287s
Keywords: (3GdcaGjI GdEfJGLjIs